Highly sensitive, localized surface plasmon resonance fiber device for environmental sensing, based upon a structured bi-metal array of nano-wires - Allsop, Thomas P.; Neal, Ron M.; Chengbo, Mou; Kalli, Kyriacos; Webb, David J. (My University, 2014)
We demonstrate a bi-metal coated (platinum and gold or silver), localized surface plasmon resonance fiber sensor with an index sensitivity exceeding 11,900 nm/RIU, yielding an index resolution of 2 × 10-5 in the aqueous index regime. This is one of the highest index sensitivities achieved with an optical fiber sensor. The coatings consist of arrays of bi-metal nano-wires (typically 36 nm in radius and 20 μm in length), supported by a silicon dioxide thin film on a thin substrate of germanium, the nano-wires being perpendicular to the longitudinal axis of the D-shaped fiber.
Keywords: Environmental sensing; Fiber devices; Localized surface plasmon resonance; Metal arrays